Exploring Children's Experiences Through Cooking Class Activities at Rocket Chicken Restaurant in Developing Fine Motor Skills - Laily Wakhidah; R Agustinus Arum Eka Nugroho (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Fine motor development requires meaningful hands-on learning experiences in early childhood education. This study aimed to analyze the implementation of cooking class activities at Rocket Chicken Restaurant and their contribution to children's fine motor skill development. A descriptive qualitative approach was employed using observation, interviews, and documentation. The participants were children from Triguna Kindergarten, Kendal Regency, who participated in cooking class activities. The findings revealed that activities such as stirring, mixing, arranging, and serving food effectively enhanced hand-eye coordination, manipulative skills, and fine muscle strength. In addition, the activities fostered children's independence, creativity, and self-confidence. Teacher readiness, adequate facilities, and collaboration with the restaurant supported the program's success, while time limitations, supervision demands, and differences in children's abilities emerged as challenges. The study concludes that cooking classes provide an effective and enjoyable contextual learning experience for promoting fine motor development in early childhood. Future research is recommended to involve broader educational settings to further explore the benefits of cooking-based learning activities.